A3.8 Association between clinical, histopathological and molecular features in primary Sjögren’s Syndrome: a retrospective study - Carubbi, Francesco; Alunno, Alessia; Cipriani, Paola; Di Benedetto, Paola; Ruscitti, Piero; Berardicurti, Onorina; Bistoni, Onelia; Caterbi, Sara; Bartoloni, Elena; Gerli, Roberto; Giacomelli, Roberto (Annals of the rheumatic diseases, 2014)
Background and Objectives Although minor salivary gland (MSG) biopsy is the diagnostic gold standard to identify focal lymphocytic sialoadenitis (FLS) in primary Sjögren’s syndrome (pSS), the association between MSG histopathology and clinical picture is still unknown. Histological studies are based on hematoxilin and eosin (H&E) staining, however new approaches such as immunofluorescence or molecular biology assays, allow to stratify pSS patients according to other variables including germinal center (GC)-like structure presence and cytokine expression. Such evaluation may represent a powerful tool to be employed in clinical practice in order to predict pSS clinical picture and eventually disease prognosis. We aimed to investigate the relationship between the characteristic of the immune infiltrate, GCs presence, molecular expression of cytokines involved in inflammation and lymphoneogenesis, laboratory and clinical features in a large cohort of pSS patients. Materials and Methods 104 pSS patients were retrospectively evaluated and 40 subjects with sicca symptoms (20 with normal MSGs and 20 with non-specific chronic sialoadenitis (NSCS)) acted as controls. H&E stained sections were assessed for histological pattern (normal, NSCS, FLS), Chisholm and Mason grading system, Tarpley score, a grading for the severity of inflammatory infiltrate and the focus score. Immunofluorescence staining for CD3, CD20 and CD21 was performed to identify the grade of lymphoid organization and the presence of GCs. Part of MSGs were processed for real time PCR testing LTa, LTb, BAFF, CXCR4, CXCL12, CXCR5, CXCL13, CCR7, CCL19 and CCL21. Results pSS patients displayed higher levels of all cytokines compared to normal MSGs and non- specific glandular inflammation according to the different histological scores (all p<0.0001). pSS patients also displayed a peculiar inflammatory scenario characterised by B/T cell segregation and GC presence. All cytokines were more expressed in pSS samples displaying GCs compared to pSS without GCs (all p<0.0001). Univariate analysis revealed that GC presence was associated with autoantibodies, hypergammaglobulinemia, salivary gland swelling, Tarpley score, focus score, and extraglandular involvement. At multivariate analysis the only clinical variable independently associated with GCs was extraglandular involvement. Conclusions In pSS histopathologic features, mainly GC presence, are associated with a peculiar cytokine expression pattern and a severe clinical subset of the disease.